Straightforward Synthesis of 2-Acetyl-Substituted Benzo[b]thiophenes - Debray, Julien; Lemaire, Marc; Popowycz, Florence (Synlett, 2013)
Described herein is a green one-step protocol for the preparation of substituted 2-acetylbenzo[b]thiophenes from commercially available aromatic halides. This efficient method has the advantage of using water as the reaction medium, resulting in a high yield of pure cyclized products. Two scaffold types have been prepared using this general procedure: 2-acetylbenzo[b]thiophenes and 2-acetyl-3-aminobenzo[b]thiophenes, both crystallized directly from the reaction mixture, due to their low solubility with water, and without the need for an additional purification step.
Keywords: heterocycles; benzo[b]thiophene; nucleophilic aromatic substitution; thiol; cyclization